On well-rounded lattices and lower bounds for the minimum norm of ideal lattices - Alves, Carina [UNESP] (2025)
In this paper, we study properties of well-rounded ideal lattices focusing on the lower bounds for their minimum norm. We present counterexamples showing that the stated bounds in a previous work do not hold for mixed number fields through the canonical embedding. However, we prove that ideal lattices obtained via the Minkowski embedding (instead of the canonical embedding) are well-rounded if and only if the number field is cyclotomic. Additionally, we derive new lower bounds for the minimum norm of ideal lattices under both the canonical and twisted embeddings. Our results not only refine existing theories but also open new possibilities for research on well-rounded ideal lattices in higher dimensions.